Perancangan Aplikasi Pengelolaan Penelitian dan Pengabdian Kepada Masyarakat Berbasis Web dan Mobile - Alvin Alvin; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Research and community service management web and mobile based is an application created to simplify submission report of research and community service. This paper presents a system for research and community service management to make report submission of research team easier by uploading their report through website, and help reviewer to do report assessment through website application. The web-based application designed with PHP programming language and Android for mobile programming language. With the existence of this application, submission and assessment report will be easier for researcher and reviewer